Sosialisasi dan Pemanfaatan Limbah Plastik Sebagai Pagar Ecobrick di SDN 13 Mataram - Ekhy Putri Wartiandani; Baiq Zakiya Darajat; Fariza Meilyana Restati; Galang Ijtihad; Sri Rizki; Hasnawati Hasnawati (Educational Consultant & Counseling Career (EC3) Mataram, 2025)
The issue of waste, especially plastic waste, is a very serious environmental concern in Indonesia. Plastic waste is difficult to decompose naturally and has the potential to pollute soil, water, and air, thus negatively impacting human health and ecosystems. One solution that can be implemented to reduce this impact is the 3R (Reduce, Reuse, Recycle) waste management concept, particularly through the ecobrick method. This study aims to implement the ecobrick method as an effort to manage plastic waste in a school setting, involving student participation at SDN 13 Mataram, Selaparang District, Mataram City, West Nusa Tenggara. The research method consists of three stages: planning, implementation, and reflection. In the planning stage, students were introduced to how to create fences using ecobricks. The implementation stage involved students in collecting, sorting, and tightly packing plastic waste into used bottles with the help of wooden sticks. In the reflection stage, the completed ecobricks were used as fencing for a medicinal plant garden at the school. The results showed that students were very enthusiastic and actively engaged throughout the process. In addition to reducing the amount of plastic waste, this activity also raised students’ awareness about the importance of environmental preservation. The ecobrick method proved effective as a hands-on learning tool and can serve as an innovative, educational, and practical waste management strategy for elementary schools.